Synthesis of Magnetic Composites of Chitosan-Fly Ash-Fe3O4 Nanoparticle to Improve Congo Red Dye Adsorption - Mayangsari, Novi Eka; Dira Pratiwi, Dewi One; Ashifa, Naura Aqillafasha; Ramadani, Tarikh Azis; Novitrie, Nora Amelia; Nindyapuspa, Ayu; Cahyono, Luqman (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2025)
Chitosan, an environmentally friendly adsorbent, is derived from the deacetylation of crab shell chitin. In this study, the chemical and physical properties of chitosan were enhanced through the direct compositing process of magnetic chitosan (Chi) with fly ash powder particles (FA). This research is of considerable importance in the development of environmentally friendly adsorbent materials for the treatment of wastewater contaminated with synthetic dyes, particularly azo dyes such as congo red. The utilization of crab shell waste as a source of chitosan, in conjunction with fly ash and Fe₃O₄ to form Chi-FA-Fe₃O₄ magnetic composites, has been demonstrated to exhibit considerable promise in enhancing adsorption efficiency. The magnetic composite of Chi-FA-Fe₃O₄ was characterized by XRD and SEM. The present study investigated the effect of adsorption process parameters on CR dye removal. The parameters that were investigated included contact time (30-150 minutes) and initial concentration of CR dye at an adsorbent dosage of 0.06 grams in 100 milliliters and a pH of 4. The maximum removal efficiency of the Chi-FA-Fe₃O₄ composite for CR dye was recorded as 99.82% at an initial concentration of 100 parts per million (ppm) CR dye for 150 minutes. Pursuant to the analysis of XRD, it has been confirmed that the compositing process was successfully executed, thereby yielding 2θ values indicative of Fe₃O₄ and FA. Additionally, an enhancement in the intensity of the Chi-FA-Fe₃O₄ composite was observed following the adsorption of CR dye. Concurrently, SEM analysis revealed that the Chi-FA-Fe₃O₄ composite and the Chi-FA-Fe₃O₄ composite exhibited an augmented intensity.